The glycosylphosphatidylinositol - phospholipase C (GPI-PLC) in bloodstream forms of Trypanosoma brucei - Hanrahan, Orla (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2007)
The localization of the GPI-PLC in bloodstream form trypanosomes was investigated using confocal microscopy and surface labelling techniques, namely biotinylation and iodination. The confocal data indicate that the GPI-PLC is exclusively located on the flagellar membrane rather than the pelicular membrane of the cell body or the flagellar pocket membrane. This location places the GPI-PLC and the VSG on the same side of the plasma membrane bilayer covering the flagellum, thereby indicating that both enzyme and substrate reside in close proximity making the cleavage reaction of the GPI-PLC on the GPI anchor a much more feasible process than previously thought. The GPI-PLC did not co-localize with the para-flagellar rod, a large structure found within the flagellum of bloodstream form trypanosomes. The GPI-PLC was found to lie closer to the cell body than the paraflagellar rod.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin